The Practice of the King's Meal at Mari: A System of Food Distribution in the Second Millennium B.C. - Glaeseman, R. R.
Diss.; dir. G. Buccellati; University Microfilms 78-20,220. - Cf. Diss Abstr 39 (1978-79) 3005f.-A.